2012
DOI: 10.1063/1.4759268
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the physical mechanism of THz generation by dual-color ultrashort laser pulses

Abstract: We experimentally verified the physical mechanism of the dual-color ultrashort laser-driven THz wave generation in air by measuring its dependence on the dual-color field phase difference. Our results evidenced that the THz generation from the laser-induced plasma is dominated by the photo-current mechanism. A continuous rotation of THz polarization was observed by changing the dual-color phase difference, facilitating coherent control of the THz intensity and polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…With a π/2 relative phase, the pump field exhibits a temporal asymmetry around the electric field maxima and the current density J (t) develops a low-frequency component due to the stepwise increase of the electron density. This component is then the major THz source [35]. Following the local current theory [23], ionization happens near the relative extrema of E(t) at the instants t 1 , t 2 , t 3 , .…”
Section: Increase In the Pump Wavelengthmentioning
confidence: 97%
“…With a π/2 relative phase, the pump field exhibits a temporal asymmetry around the electric field maxima and the current density J (t) develops a low-frequency component due to the stepwise increase of the electron density. This component is then the major THz source [35]. Following the local current theory [23], ionization happens near the relative extrema of E(t) at the instants t 1 , t 2 , t 3 , .…”
Section: Increase In the Pump Wavelengthmentioning
confidence: 97%
“…As a first example, figure 3(a) shows the efficiency factor g THz plotting separately the integrals ofR andÎ for a classical two-color pulse with f = 0 1 . We retrieve the best SH phase angle f p = 2 2 for THz production by photocurrents [30], which induces a substantial increase inN e L at FH frequency, hence inR. Indeed, if we apply the approximation that ionization occurs at the maxima of E L 2 and neglect the envelope effects, Another example illustrates in figure 3(b) the spectrum of the electron density computed on the first harmonics of a sawtooth wave shape, known to supply the highest THz yields to date at fixed ionization level [29].…”
Section: An 'Optical' Criterion To Evaluate the Laser-to-thz Conversimentioning
confidence: 99%
“…However, measurement of Δϕ at the generation point is a very difficult task. In [23], the authors have claimed that Δϕ at the generation point was successfully obtained and concluded that the photocurrent model is the dominant process for the THz generation through two-color filamentation. However, π∕2 phase shift at SHG [24] and Gouy phase shift are not taken into account at the phase determination.…”
mentioning
confidence: 99%